(untitled) (World Science, 2019)
In order to reduce imparai after performing mastectomy, we have proposed a scheme of intravenous drip of Solu - medrol: 125 mg once a day for 3 days, followed by an interval every other day until the ninth day of the postoperative period. The use of this scheme of conservative treatment allowed to stop the clinical manifestations of imparai on the tenth day of the postoperative period.